The predictive value of 24-hour urinary calcium for kidney stone risk in primary hyperparathyroidism: insight from a retrospective study of parathyroid adenoma cases - Bhan, Arti; Simon, Rebecca; Yaseen, Aseel; Cook, Bernard; Qiu, Shijing; Rao, Sudhaker D. (Frontiers in Endocrinology, 2025)
BackgroundPrimary hyperparathyroidism (PHPT) is associated with an increased risk of kidney stones. However, the clinical utility of 24-hour urinary calcium (24h-UCa) as a predictor of nephrolithiasis, and its role in surgical decision-making, remains uncertain due to inconsistent findings.ObjectiveTo evaluate whether 24h-UCa is a reliable disease-specific predictor of kidney stone risk in patients with PHPT and to identify demographic and biochemical determinants of urinary calcium excretion.MethodsThis retrospective study included 306 PHPT patients who underwent curative parathyroidectomy for confirmed adenoma. Demographics, kidney stone history, and biochemical data were collected. T-tests, chi-square tests, multivariate logistic regression, and multiple regression were used to analyze associations of 24h-UCa with kidney stones, demographic, and biochemical indices.ResultsKidney stones were present in 22% of patients. No significant difference in 24h-UCa was observed between stone-formers and non-stone-formers, even after adjustment for age, gender, and race. In contrast, 24h-UCa was significantly higher in men and white patients, with hypercalciuria more prevalent among white individuals. Serum calcium and eGFR were also significantly positively associated with 24h-UCa.ConclusionOur results suggest that 24h-UCa is not an independent predictor of kidney stone risk in PHPT and is largely influenced by demographic and biochemical factors. Accordingly, routine 24h-UCa measurement for evaluating patients with sporadic PHPT or for guiding parathyroidectomy decisions is not recommended. This study is limited by its retrospective design, reliance on a single urine collection, and lack of detailed dietary or genetic data, which may have introduced variability and reduced power to detect weak associations.